A high-performance, cobalt-free cathode for intermediate-temperature solid oxide fuel cells with excellent CO2 tolerance - Bu, Yun-fei; Zhong, Qin; Chen, Dong-Chang; Chen, Yu; Lai, Samson Yuxiu; Wei, Tao; Sun, Hai-bin; Ding, Dong; Liu, Meilin (Journal of power sources, 2016)
Compared with some cobalt-rich cathodes which have been proven to yield high performance in SOFCs, interest in cobalt-free cathodes has increased due to their reduced thermal expansion coefficients (TECs), high structural stability, and CO2 tolerance. In this report, a new robust Co-free complex perovskite oxide PrLa0.4Ba0.6Fe0.8Zn0.2O5+δ (PLBFZ) has been synthesized and evaluated. The TEC is 14.4 × 10−6 K−1. With the introduction of Sm0.2Ce0.8O2 (SDC), the composite cathode PLBFZ-SDC with a mass ratio of 7:3 (PLBFZ-SDC 73) exhibited the best electrocatalytic activity for oxygen reduction under OCV conditions, with polarization values of 0.044, 0.079, 0.124, 0.251, 0.572, and 1.297 Ω cm−2 at 800, 750, 700, 650, 600, and 550 °C, respectively. The power densities of the cell were 1309, 1079, 788 and 586 mW cm−2 at 750, 700, 650, and 600 °C, respectively. Moreover, it appears to have good stability in air containing 1% CO2 (volume ratio) for 150 h based on Raman and polarization resistance (Rp) analysis. These results suggest that PLBFZ and its SDC composite are promising cathodes for IT-SOFCs. •PLBFZ–SDC was evaluated as a cathode for IT-SOFC firstly.•Thermal expansion coefficients of PLBFZ are lower than cobalt-containing cathodes.•The PLBFZ appears a certain ability of CO2 tolerance.•The ORR and cell performance were improved by the doping Pr into the A site of LBFZ.